Multiscale modeling of thermo-hydromechanical behavior of clayey rocks and application to geological disposal of radioactive waste - Jianfu Shao; Zhan Yu; Minh-Ngoc Vu (Journal of Rock Mechanics and Geotechnical Engineering)
This work is devoted to numerical analysis of thermo-hydromechanical problem and cracking process in saturated porous media in the context of deep geological disposal of radioactive waste. The fundamental background of thermo-poro-elastoplasticity theory is first summarized. The emphasis is put on the effect of pore fluid pressure on plastic deformation. A micromechanics-based elastoplastic model is then presented for a class of clayey rocks considered as host rock. Based on linear and nonlinear homogenization techniques, the proposed model is able to systematically account for the influences of porosity and mineral composition on macroscopic elastic properties and plastic yield strength. The initial anisotropy and time-dependent deformation are also taken into account. The induced cracking process is described by using a non-local damage model. A specific hybrid formulation is proposed, able to conveniently capture tensile, shear and mixed cracks. In particular, the influences of pore pressure and confining stress on the shear cracking mechanism are taken into account. The proposed model is applied to investigating thermo-hydromechanical responses and induced damage evolution in laboratory tests at the sample scale. In the last part, an in situ heating experiment is analyzed by using the proposed model. Numerical results are compared with experimental data and field measurements in terms of temperature variation, pore fluid pressure change and induced damaged zone.